2016
DOI: 10.1042/bsr20160345
|View full text |Cite
|
Sign up to set email alerts
|

Association between selenium intake and the risk of pancreatic cancer: a meta-analysis of observational studies

Abstract: Quantification of the association between the intake of selenium and risk of pancreatic cancer is still conflicting. Thus, we conducted a meta-analysis to summarize the evidence from epidemiological studies of selenium intake with the risk of pancreatic cancer. Pertinent studies were identified by a search of PubMed and Web of Knowledge to July 2016. The random-effect model was used. Sensitivity analysis and publication bias were conducted. Data from six studies including 1424 pancreatic cancer cases were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…Compared with inorganic Se, Se-yeast is less toxic, exhibits higher bioavailability, and can maintain Se levels for a longer period after the cessation of supplementation . Currently, Se-yeast is mainly used to treat Keshan disease, prevent cancer, or modulate immune responses. On the basis of our previous studies, Se-Met, the major form of Se in Se-enriched yeast, effectively improved cognitive dysfunction and neuropathology in the triple transgenic mouse model of AD (3×Tg-AD mice). , These studies of the effects of the Se compound on subjects with AD indicated that Se-yeast has great potential as a treatment for AD, but the exact effects and underlying mechanisms remain poorly understood. In this study, we explored the effect of Se-yeast on AD pathology and found that long-term dietary supplementation with Se-yeast improved the cognitive abilities of 3×Tg-AD mice by reducing tau hyperphosphorylation, improving neuronal activity, and mitigating synaptic deficits, revealing a therapeutic effect of Se-yeast on a mouse model of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with inorganic Se, Se-yeast is less toxic, exhibits higher bioavailability, and can maintain Se levels for a longer period after the cessation of supplementation . Currently, Se-yeast is mainly used to treat Keshan disease, prevent cancer, or modulate immune responses. On the basis of our previous studies, Se-Met, the major form of Se in Se-enriched yeast, effectively improved cognitive dysfunction and neuropathology in the triple transgenic mouse model of AD (3×Tg-AD mice). , These studies of the effects of the Se compound on subjects with AD indicated that Se-yeast has great potential as a treatment for AD, but the exact effects and underlying mechanisms remain poorly understood. In this study, we explored the effect of Se-yeast on AD pathology and found that long-term dietary supplementation with Se-yeast improved the cognitive abilities of 3×Tg-AD mice by reducing tau hyperphosphorylation, improving neuronal activity, and mitigating synaptic deficits, revealing a therapeutic effect of Se-yeast on a mouse model of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationship between selenium and tumors has been widely reported in epidemiological studies [36][37][38][39][40], the evidence of taking selenium as an anticancer drug alone seems to be insufficient. Reports of MSC have described the anti-tumor effect associated with irinotecan through the affection of the tumor microenvironment (TME), including the inhibition of angiogenesis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Han X et al originally reported anti-PDAC effects of selenium (128,129). A meta-analysis and a later nested case-control study found no adverse effect on PDAC but a negative association was apparent for patients with body mass index (BMI) higher than 25 (130,131). Beneficial effects and no adverse effects have also been reported against diabetes (132)(133)(134).…”
Section: Seleniummentioning
confidence: 99%